What is boredom of the older person residing in long-term care? The development of a theoretical definition and a conceptual model. - Stevenson, Heather (2008)
In an ageing and "chronologically gifted" population (Lewis, 1998 cited in Tavormina 1999), quality of life for residents in long-term care facilities is under scrutiny. Boredom specifically has been identified as an issue for residents. Interventions have been introduced to alleviate boredom and long-term care facilities have also adopted philosophies of care to tackle perceived boredom. The familiar image of passive older residents sitting in chairs for most of the day, may summon up the concept of boredom. Boredom has been insinuated not only from its reporting but also from research that demonstrates a large amount of inactivity in this population.